Penyakit daun yang disebabkan oleh jamur dan pengendaliannya pada pembibitan pisang cavendish di PT Great Giant Foods (GGF) - Rachmadina, Najma Fadya; Nurdin, Muhammad; Ginting , Cipta; Aeny, Titik Nur (Jurnal Proteksi Agrikultura, 2025)
Leaf diseases in banana seedlings is one of the most serious problem in PT GGF because the cost of post-planting field control will be very high if disease control in the nursery is not effective. This study aims to determine banana leaf diseases caused by fungi in nurseries at PT GGF, the efficacy of seven fungicide active ingredients to control banana leaf diseases in nurseries, and the cost of controlling leaf diseases on the health of banana seedlings in nurseries. The research was conducted from February to September 2024 at GGF in Central Lampung. Disease diagnosis is carried out by taking samples of leaves of banana seedlings with spotting or other symptoms and following Koch’s postulates. In the efficacy trial of seven fungicide active ingredients, the treatments were arranged using a completely randomized design (RAL) with nine treatments and two replications. Efficacy test were conducted using two treatments that differed in the way the fungicides were applied. The observed variables were disease incidence, healthy leaf rate, and average number of leaves per plant to determine the cost of control on banana seedling health. The results showed that pathogenic on banana seedlings, namely Fusarium, Curvularia, Nigrospora, and several fungi that have not been identified. The efficacy test of seven fungicide active ingredients in the control treatment was significantly different from captan, tiram liquid, tiram powder, and mancozeb so that several kinds of fungicide active ingredients can be used as alternative fungicides to control freckles on banana seedling leaves which can then be tested further. The cost of disease control per seedling was found to be between Rp1.190-1.210, but this cost did not provide any control over seedling health.